In-Silico Study of N-Hydroxysuccinimide Folate and GAPDH as Targeting Agents for Tuberculosis Treatment - Marhaendra, Laurentius Ivan Ageng; Muchtaridi, Muchtaridi; Rosandi, Yudi; Gazzali, Amirah Mohd (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Tuberculosis remains a major public health concern due to emerging cases of drug resistance. To overcome this issue, the effectiveness of antitubercular medications must be reinforced. One of the methods that can be used is using active targeting, which involves small molecules that bind to a specific receptor. In this research, we study the potential of N-hydroxysuccinimide (NHS) folate to be used as the targeting agent against the GAPDH (glyceraldehyde-3-phosphate dehydrogenase) cell-surface receptor, a common virulence factor found on many pathogenic bacteria, including Mycobacterium tuberculosis. We conducted this research using computational methods, specifically molecular docking and molecular dynamics simulation. Based on the evaluation of molecular docking and molecular dynamics simulation results, NHS-folate is predicted to have a huge potential to be an active targeting agent against the GAPDH receptor of Mycobacterium tuberculosis.